Food Regulatory Agencies and Steps to Opening a Food Business in Florida: FSHN22-2/FS435, 2/2022 - Krug, Matthew; Hagen, Jennifer; Ellis, Sarah M. (EDIS, 2022)
In Florida, three main agencies enforce food safety regulations and license food businesses. Each agency enforces regulations pertaining to a different sector of food businesses. With three agencies enforcing similar rules, food entrepreneurs often struggle to find the correct information needed to obtain a license to open a food business. This new 3-page publication of the UF/IFAS Food Science and Human Nutrition Department intends to introduce food entrepreneurs to the various agencies in Florida that regulate food businesses and provide a brief overview of the steps to open a food business in Florida. Written by Matthew D. Krug, Jennifer Hagen, and Sarah M. Ellis. https://edis.ifas.ufl.edu/fs435